Mosh Azim / Muhammad Afiq Asyraf Jamali - Jamali, Muhammad Afiq Asyraf (2021)
First and foremost, let us have a clear view on what entrepreneur. Entrepreneur is a person who set up a business or businesses in order to making profit as their main goals. An entrepreneur is someone who develops a business model, acquires the physical and human capital needed to start a new business, operates it, and is responsible for its success or failure. (Juneja, 2015). An entrepreneur should be knowledgeable in order for them to grow up their business bigger and bigger. As global, there are a lot of successful entrepreneur such as Jeff Bezos the founder of Amazon, Elon Musk founder of Space-X and the Co-founder of PayPal and Tesla, Mark Zuckerberg the technology entrepreneur who is own Facebook and currently known as Meta and many more. In Malaysia, there are also a lot of entrepreneur from various background such as Fizo Omar, Dato Seri Alif Syukri, Dato Seri Siti Nurhaliza and many more. In this study case, the entrepreneur I choose is Mosh Azim. A dedicated gentleman who is very obsessed with his business. Service type business is his forte but at the same time he also has 2 products under the same brand. His brand and company name is MSA Ventures. MSA Ventures is a professional event management company that specializes in a range of events for instance, wedding ceremonies, corporate events and private functions. They mainly provide services such as audio visual consultation, multimedia equipment installation, PA system and live feed video as well as emcee and other services according to their respective client’s request. Besides that, MSA Ventures also come out with two new products which are Apam Bakar and also Acar Buah. In order to run his business, I identified 4 competencies that possibly being used by him such as initiative, commitment to work contract, systematic planning, use of influence strategies. According to my research and interview session with him, I am very confident all these competencies has helped him a lot to grow up his business since 2013 until today. The brand of MSA Ventures has been a popular company especially for the event management service. So, in this study case, I will explain in details regarding Mosh Azim, MSA Ventures and the all competencies as I mentioned above.